THE EFFECT OF BOARDGAMES THERAPY: SCRABBLE ON COGNITIVE ABILITIES IN ELDERLY WITH DEMENTIA - Jannah, Eka Sindi Miftahul; Anwar, Syamsul; Herlina, Lily (Poltekkes Kemenkes Bandung, 2025)
Cognitive impairment in the elderly causes a decrease in the ability to do various things related to thinking and remembering. Dementia is a term used to describe memory decline in the elderly. Prevention of cognitive impairment can be done by using media that stimulate brain activity. Scrabble is a type of board game that emphasizes initiative, creativity, planning, and flexibility in dealing with success or failure while being entertaining.This study aims to determine the effect of board games (scrabble) on increasing cognitive capacity in the elderly with dementia. The study was conducted at Tresna Werdha Budi Mulia 2 Jelambar, West Jakarta during January-July 2023. The target of the study was the elderly living in nursing homes. Using the Generalized Linear Model (GLM) analytical method, this study design used a quasi-experiment with a two-stage approach. Group pretest-posttest design approach. The sample consisted of 31 elderly in the control group and 31 elderly in the intervention group. The sampling strategy was random using the two-population proportion formula. The research instrument used was the Mini Mental Status Examination (MMSE) questionnaire. Nine therapy sessions were given, and the eighth session showed a significant improvement after the implementation of scrabble game therapy. Statistical test using Paired T-test p-value of 0.000 < (α) 0.05 showed that board games (scrabble) can improve cognitive capacity in elderly with dementia. Broad-games therapy: Scrabble can be routinely recommended to be included in daily activities for the elderly so that it can delay the severity of dementia.